Intracranial Stenting: Angioplasty Basic Technique, Indications, and Sizing: 2-Dimensional Operative Video. Issue 2 (6th May 2021) - Dossani, Rimal H; Waqas, Muhammad; Cappuzzo, Justin M; Sonig, Ashish; Siddiqui, Adnan H; Levy, Elad I; Davies, Jason M; ,
Abstract: Intracranial atherosclerotic disease (ICAD) is a common cause of stroke. Antiplatelet therapy is the mainstay for symptomatic ICAD treatment. Endovascular management with submaximal angioplasty and/or intracranial stenting is reserved for patients with repeated ischemic events despite optimal medical therapy. We demonstrate intracranial angioplasty and stenting technique, technique indications, and sizing of stent and target vessel diameter. Stenting and angioplasty have been described in the Stenting and Aggressive Medical Management for Preventing Recurrent Stroke in Intracranial Stenosis and Wingspan Stent System Post Market Surveillance trials. 1, 2 Submaximal angioplasty has also been described. 3 This patient, who had been on dual antiplatelet therapy for several months, initially presented with occlusion of the left middle cerebral artery M2 inferior division and underwent mechanical thrombectomy with successful reperfusion. Postoperatively, the patient's symptoms did not improve. Medical management was optimized with heparin infusion. However, repeat stroke study demonstrated M2 inferior division reocclusion. A decision was made to proceed with intracranial angioplasty and stenting. P2Y12 levels were therapeutic. Under moderate conscious sedation, submaximal angioplasty of up to 80% of the normal M2 caliber was attempted. However, we observed persistent high-grade stenosis of the M2 inferior division. The major risk of crossing the lesion for angioplasty is vessel perforation. To safely perform this maneuver, we used a J-configured Synchro-2 microwire (Stryker). Because of the patient's recent thrombectomy, we also had prior tactile feedback about how much resistance was encountered while crossing the occlusion. We then deployed a balloon-mounted intracranial stent for optimal radial force across the stenotic area to restore perfusion. Postoperative computed tomography perfusion showed resolution of the previously noticed perfusion deficit. The patient gave informed consent for the procedures and video recording. Institutional review board approval was deemed unnecessary. Video. ©University at Buffalo Neurosurgery, September 2020. With permission.